Teachers’ Challenges and Innovative Strategies in Delivering Islamic Religious Education at Kenanga Kindergarten, Balikpapan - Salsabila, Rara; Haeruddin, Hendra (Journal of Educational Research and Practice, 2024)
This article explains what are the challenges for a teacher in teaching PAI to early childhood and what innovations have been developed to overcome these problems. This research is intended as knowledge material for prospective teachers in dealing with and responding to early childhood, especially in learning Islamic Religious Education (PAI). The method used is a qualitative method with a focused interview approach. Data collection techniques through observation, interviews and documentation. Based on the results of the research that has been carried out, the author draws the following conclusions: These challenges include teachers needing to prepare a curriculum that is fun for children, creating learning methods that are appropriate to the level of development of children, maintaining children's attention so that it remains focused. in learning, creating a conducive classroom environment so that learning runs optimally, and explaining the importance of tolerance and mutual respect for people of different religions. In this case, innovation is the key to overcoming these challenges. Teachers need to develop interesting and interactive learning strategies so that children can more easily understand Islamic religious concepts.